A comprehensive search for the radio counterpart of GW190814 with the Australian Square Kilometre Array Pathfinder. Issue 3 (14th December 2021) - Dobie, D; Stewart, A; Hotokezaka, K; Murphy, Tara; Kaplan, D L; Buckley, D A H; Cooke, J; Ho, A Y Q; Lenc, E; Leung, J K; Gromadzki, M; O'Brien, A; et al.
ABSTRACT: We present results from a search for the radio counterpart to the possible neutron star–black hole merger GW190814 with the Australian Square Kilometre Array Pathfinder. We have carried out 10 epochs of observation spanning 2–655 d post-merger at a frequency of 944 MHz. Each observation covered 30 deg 2, corresponding to 87 per cent of the posterior distribution of the merger's sky location. We conducted an untargeted search for radio transients in the field, as well as a targeted search for transients associated with known galaxies. We find one radio transient, ASKAP J005022.3−230349, but conclude that it is unlikely to be associated with the merger. We use our observations to place constraints on the inclination angle of the merger and the density of the surrounding environment by comparing our non-detection to model predictions for radio emission from compact binary coalescences. This survey is also the most comprehensive widefield search (in terms of sensitivity and both areal and temporal coverage) for radio transients to-date and we calculate the radio transient surface density at 944 MHz.